Association and Correlation of Thyroid Hormones with Anaemia Types in Pregnant Women - Prabhavathi V; Prasad DKV (New Horizons in Medicine and Medical Research Vol. 5, 2022)
The present study aimed to measure the prevalence of thyroid dysfunction and to study their association with anaemia types in pregnant women. In this study, Three hundred and eighty pregnant women with a gestational age of 12 weeks who had no history of thyroid dysfunction or anaemia were chosen. All pregnant women were divided into two groups: A, euthyroid, and B, thyroid dysfunction. According to the nature of the dysfunction, the B group was further subdivided into hypothyroid, subclinical hypothyroid (SCH), and hyperthyroid. Thyroid hormones and erythrocyte indices were measured in all subjects using 5 mL of blood. According to the findings, Out of 380 participants, 77.9% were found to be euthyroid, while the remaining 22.1 %had thyroid dysfunction. Hypothyroidism was detected in 7.9% of the cases, SCH in 13.9 %, and hyperthyroidism in 0.3 %of the cases. Anemia was found in 97 pregnant women (32.8 %) out of 296 euthyroid women, whereas it was found in 43 women out of 84 (51.2 %) in thyroid dysfunction women, that is significant statistically. There was no statistically significant difference between the thyroid dysfunction groups in Hb concentration, RBC count, MCV, MCH, and PCV between euthyroid and different thyroid dysfunction conditions (p<0.05). The correlation between fT4 and erythrocyte indices was found to be statistically significant. Because fT4 and TSH are correlated with erythrocyte indices, screening for thyroid dysfunction and vice versa is recommended to avoid the complications associated with anaemia and thyroid dysfunction.